Lion's mane (Hericium erinaceus) as a potential protective against metronidazole-induced toxicity in brain and testes of male rats: Protein expression and biochemical evaluation - Ligia E. Shemiss; Sanaria H. Al Katy; Saraa H. Barsoom; Melen M. Markus; Amani L. Hameed (Iraqi Journal of Veterinary Sciences)
Lion's mane (Helicium erinaceus) is a highly medicinal fungus with diverse bioactive molecules that have been proven to be beneficial in neurodegenerative diseases. Thus, the current study’s objective was to probe the potential function of this mushroom in the protection of the brain, and we screened its effect on testes in metronidazole-induced toxicity. Adult male Albino Wistar rats were divided into four groups, each containing six animals. In the control group, rats were administered distilled water; the second group was given metronidazole at a dose of 500mg/kg body weight; the third and fourth groups were administered Lion’s mane at 1 and 1.5g/kg, respectively. Two hours later, metronidazole was given at a dose of 500mg/kg. Metronidazole and Lion’s mane were given orally for 40 consecutive days. Results of the open field test showed significant neurobehavioral alterations in Lion’s mane-treated rats. Lion's mane at 1g/kg mitigated histological damage in the brain and preserved testosterone levels, whereas 1.5g/kg showed adverse effects on the testes. All treated groups showed relatively the same intensity for expression of both p53 and Bcl-2 proteins. Notably, p53 expression was more intense at 1.5g/kg, while Bcl-2 expression was intense at 1g/kg. We conclude from the current study that Lion’s mane, at low doses, acts as a protective herb against metronidazole toxicity, exhibits an improvement of the histological changes, and exerts anti-apoptosis characteristics.